Primary Melanoma of the Breast Parenchyma: An Oncoplastic Approach. Issue 12 (December 2020) - Snashall, Emma; Kiernan, Tamara; Harper-Machin, Aenone; Taghizadeh, Rieka
Abstract : Summary: Primary melanoma of the breast parenchyma (PMPB) is a rare and aggressive disease, with only a few cases reported in the literature. We present the case of a 50-year old woman who underwent mastectomy and immediate breast reconstruction using a free DIEP flap following recurrence after breast conserving surgery. This report highlights the importance of an oncoplastic approach for this diagnosis and the benefit of immediate autologous breast reconstruction.